A kind of water-free disperse dye printing ink and printing process thereof

By improving the inkjet printing process and ink composition, using liquid dispersed dyes and vinyl modified sodium lignin sulfonate and other components, combined with steam-consolidation and cross-linking reaction, the water-free washing inkjet printing of polyester fabrics is achieved, solving the problems of large water and energy consumption and unclear printing patterns in traditional processes, and achieving clear patterns and good feel effects.

CN118599337BActive Publication Date: 2025-03-11ZHEJIANG YINGFENG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410695925.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-03-11
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

The traditional dispersed dye inkjet printing process consumes a lot of water and energy, and the printing pattern is unclear. Pretreatment is required to improve the water retention of the fabric to the ink and reduce anisotropy, but the traditional paste needs to be fixed after water washing and removal.

Method used

By improving the pretreatment process and printing ink, liquid dispersed dyes and vinyl modified sodium lignin sulfonate are used to combine the steam-consolidation and color fixation and crosslinking reactions in the inkjet printing process to achieve water-free washing throughout the printing process.

Benefits of technology

It achieves the clarity and good feel of the printing pattern, saves water and energy saving effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118599337B_ABST
    Figure CN118599337B_ABST
Patent Text Reader

Abstract

The invention discloses a water-free disperse dye printing ink and a printing process thereof. The disperse dye printing ink provided by the invention is used in combination with the printing process. Vinyl is introduced into a dispersant for preparing the ink and a pretreatment agent used for printing pretreatment. The two undergo a polymerization reaction in the steaming and color fixing stage to achieve two-phase crosslinking, thereby accelerating the diffusion and coloring of the disperse dye on fabric fibers, fixing the floating color at the same time, greatly improving the dye uptake rate, and achieving the purpose of water-free printing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inkjet printing, and in particular relates to a water-free disperse dye printing ink and a printing process thereof. Background Art

[0002] Polyester is widely used due to its advantages in strength, wrinkle resistance, ironing resistance, thermoplasticity, etc. In the textile industry, most polyester needs to be processed by printing to improve its application value. The commonly used printing methods are direct printing, transfer printing, paint printing, and inkjet printing. Among them, inkjet printing is a clean production technology that is being vigorously developed in the textile industry. It has high dye utilization rate, low amount of additives added, and low wastewater and waste residue emissions. It is expected to replace traditional printing technology and become the mainstream technology.

[0003] The traditional disperse dye inkjet printing process includes steaming, baking, reduction cleaning, water washing and other steps after printing. Because the coloring mechanism of disperse dyes is to transform the fiber crystalline phase into the amorphous phase through heating, and the disperse dye diffuses into the amorphous area to achieve dyeing, the steaming and baking are for phase transformation and promoting dye diffusion, and the role of the two-step washing is to remove floating colors. This process consumes a lot of water and energy, which is not conducive to environmental protection and energy saving. In addition, since the fibers on the surface of polyester fabrics are arranged in warp and weft directions and have poor affinity for ink, it is easy to cause ink penetration and diffusion, and ultimately lead to unclear printed patterns. Therefore, the fabric needs to be pre-treated. Usually, a hydrophilic paste is used for surface treatment to improve the fabric's water retention of ink and reduce anisotropy, but the traditional paste needs to be washed after color fixation.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The invention improves the pretreatment process and printing ink to achieve the purpose of washing-free printing in the whole process, and the obtained printing pattern is clear and has good hand feeling.

[0006] The present invention can be implemented like this:

[0007] In a first aspect, the present invention provides a liquid disperse dye, which comprises the following components calculated by mass percentage: 8wt% to 12wt% disperse dye, 5wt% to 15wt% vinyl modified sodium lignin sulfonate, 0.1wt% to 0.5wt% defoamer, and the balance is deionized water.

[0008] In an optional embodiment, the disperse dye is selected from at least one of a low-temperature disperse dye, a medium-temperature disperse dye, and a high-temperature disperse dye. Preferably, the disperse dye is a high-temperature disperse dye.

[0009] In an optional embodiment, the liquid disperse dye comprises at least one of the following features:

[0010] Feature 1: The average particle size is 100-500nm, preferably 100-300nm;

[0011] Feature 2: Particle size dispersion index (PDI) is 0.2 to 0.3, preferably 0.2 to 0.25.

[0012] The method for preparing vinyl-modified sodium lignin sulfonate comprises the following steps:

[0013] Sodium lignin sulfonate is weighed and dissolved in a solvent, and a base is added, and the mixture is stirred and dissolved under an inert atmosphere, and then vinyl ethylene oxide is added to carry out a ring-opening reaction. After the reaction is completed, the reaction solution is purified and dried to obtain vinyl-modified sodium lignin sulfonate.

[0014] In an optional embodiment, the solvent is selected from at least one of ethanol, water, DMF, chloroform and DMSO.

[0015] In an optional embodiment, the base is selected from one of NaOH and KOH.

[0016] In an optional embodiment, the ring-opening reaction refers to reacting at 60-80° C. for 24-36 hours.

[0017] In an optional embodiment, the mass ratio of sodium lignin sulfonate, vinyl ethylene oxide and alkali is 1:0.2 to 0.4:0.02.

[0018] In an optional embodiment, the defoaming agent is selected from one or a combination of emulsified silicone oil, tributyl phosphate, and higher alcohols; in some embodiments of the present invention, one of the defoaming agents KYC-710 and defoaming agent Y-690 / 691 is used.

[0019] In a second aspect, the present invention provides a method for preparing a liquid disperse dye, comprising the following steps:

[0020] Weigh disperse dye, vinyl modified sodium lignin sulfonate, defoamer and deionized water to obtain wet material, grind the wet material to obtain liquid disperse dye.

[0021] In an optional embodiment, the grinding includes at least one of ball milling and sand milling.

[0022] In an optional embodiment, the ball milling conditions include: a rotation speed of 400-800 rpm, a grinding ball diameter of 100-300 μm, a grinding ball of 100%-150% of the mass of the wet material, and a ball milling time of 14-24 h.

[0023] In a third aspect, the present invention provides a disperse dye printing ink, which comprises the following components calculated by mass percentage: 25wt% to 35wt% of liquid disperse dye, 10wt% to 15wt% of moisturizer, 0wt% to 0.7wt% of viscosity regulator, 0.2wt% to 0.6wt% of surfactant, 0.02wt% to 0.07wt% of pH regulator, 0.1wt% to 0.3wt% of defoaming agent, and the balance is water.

[0024] In an optional embodiment, the disperse dye printing ink includes at least one of the following features:

[0025] Feature 1: Zeta potential is -40~-56mV;

[0026] Feature 2: Surface tension is 30-35mN / m;

[0027] Feature 3: Viscosity is 1.5-2.2 mPa·s;

[0028] Feature 4: Conductivity is 6-7μS / cm;

[0029] Feature 5: pH value is 7-9.

[0030] In an optional embodiment, the humectant is selected from at least one of ethylene glycol, butylene glycol, propylene glycol, glycerin, and diethylene glycol.

[0031] In an optional embodiment, the viscosity modifier is selected from at least one of polyethylene glycol and polyvinyl pyrrolidone.

[0032] In an optional embodiment, the surfactant is selected from at least one of fatty alcohol polyoxyethylene ether, alkyl glycoside, Span60, Tween80, and OP-10.

[0033] In an optional embodiment, the pH adjuster is selected from at least one of diethanolamine, triethanolamine, ammonia water, and trimethylamine.

[0034] In a fourth aspect, the present invention provides an inkjet printing pretreatment agent, which comprises the following components, calculated by mass percentage: 15wt% to 25wt% of silane monomer, 5wt% to 10wt% of hydrophilic polymer, 2wt% to 5wt% of catalyst, and the remainder being a mixed solution of alcohol and water.

[0035] In an optional embodiment, the silane monomer has the following characteristics at the same time:

[0036] Feature 1: The molar ratio of the silane monomer having 1 alkoxy group, the silane monomer having 2 alkoxy groups, and the silane monomer having 3 alkoxy groups is 1:4-8:1-2;

[0037] Feature 2: Silane monomer containing vinyl group.

[0038] Alkoxy refers to -OR connected to the silicon atom, R is an alkyl group, Si-OR undergoes hydrolysis condensation reaction under acid or alkaline conditions, and two (Si-OR) condense to form (Si-O-Si). Therefore, controlling the molar ratio of monomers with alkoxy numbers of 1, 2, and 3 respectively can control the degree of crosslinking and the viscosity of the formed silica sol. The higher the crosslinking strength, the more conducive it is to form a pretreatment layer with a mesoporous structure and uniform pore distribution, which is beneficial to the diffusion of disperse dyes. However, too high a crosslinking strength makes the fabric feel worse.

[0039] Examples of silane monomers containing a vinyl group include vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxydivinylsilane, methylvinyldimethoxysilane, vinyltriisopropoxysilane, diethoxymethylvinylsilane, and allyloxytrimethylsilane.

[0040] Examples of silane monomers having 1 alkoxy group include 3-aminopropyldimethylmethoxysilane, methoxytrimethylsilane, and trimethylethoxysilane.

[0041] Examples of silane monomers having 2 alkoxy groups include dimethyldimethoxysilane, diethoxydimethylsilane, 3-aminopropylmethyldimethoxysilane, and N-dimethylaminopropyl-aminopropylmethyldimethoxysilane.

[0042] Examples of silane monomers having 3 alkoxy groups include methyltriethoxysilane, methyltrimethoxysilane, hydroxymethyltriethoxysilane, and aminomethyltriethoxysilane.

[0043] In an optional embodiment, the hydrophilic polymer is selected from at least one of polyvinyl alcohol, polyethylene glycol, sodium hyaluronate, and polyacrylic acid.

[0044] In an optional embodiment, in the alcohol-water mixed solution, the alcohol is selected from ethanol, methanol, and ethylene glycol, and the mass ratio of the alcohol to water is 1:3-7.

[0045] In an optional embodiment, the catalyst is selected from one of hydrochloric acid, acetic acid, sodium hydroxide and ammonia water.

[0046] In a fifth aspect, the present invention provides a water-free inkjet printing process, comprising the following steps: padding pretreatment → first drying → inkjet printing → second drying → spraying initiator → steaming fixation → third drying.

[0047] In an optional embodiment, in the padding pretreatment step, the immersion time is 10 to 30 minutes, and the liquid carrying rate is 60 to 90%.

[0048] In an optional embodiment, the conditions for the first drying are: temperature 60-80° C., time 5-8 min.

[0049] In an optional embodiment, the second drying conditions are: temperature 60-80° C., time 3-5 min.

[0050] In an optional embodiment, the conditions for the third drying are: temperature 100-120° C., time 5-15 min.

[0051] In an optional embodiment, spraying the initiator means spraying the aqueous initiator solution uniformly on the surface of the fabric in a spraying manner, and the operation includes at least one of the following features:

[0052] Feature 1: The aqueous initiator is selected from at least one of ammonium persulfate, sodium persulfate and potassium persulfate;

[0053] Feature 2: The concentration of the initiator aqueous solution is 1wt% to 5wt%;

[0054] Feature 3: The spraying amount of the initiator aqueous solution is 0.4-0.6L / m 2 .

[0055] In an optional embodiment, steaming fixation refers to steaming in saturated steam at 102° C. and normal pressure for 10 to 20 minutes.

[0056] Principle description:

[0057] The disperse dye printing ink provided by the present invention is used in combination with a printing process, vinyl is introduced into both the dispersant and the pretreatment agent, a polymerization reaction occurs under the action of an initiator in the steaming fixation stage to achieve two-phase crosslinking, on the one hand, the dispersant is fixed in the pretreatment layer due to the crosslinking reaction, thereby releasing the disperse dye particles, and the asymmetric wettability of the pretreatment layer and the polyester fiber layer drives the disperse dye particles to migrate to the fiber layer and enter the amorphous region of the fiber to achieve fixation; on the other hand, the cross-linked pretreatment layer plays a role in bonding and fixing the floating color, thereby eliminating the water washing step; furthermore, the pretreatment agent formula provided by the present invention balances the ratio of the flexible silane segment and the hydrophilic segment, thereby having both anti-seepage property and good hand feel, and the obtained fabric printing pattern is clear and soft to the touch.

[0058] The present invention has the following advantages and beneficial effects:

[0059] (1) The dispersant provided by the present invention has a good dispersing effect on disperse dyes, and the obtained liquid disperse dyes have uniform particle size distribution and small particle size.

[0060] (2) The pretreatment agent provided by the present invention does not require water washing, and has good water holding capacity and isotropy for ink. The ink has a low degree of penetration and the obtained printed pattern is clear.

[0061] (3) The present invention provides a water-free polyester disperse dye inkjet printing process, which utilizes the chemical reaction between the pretreatment layer and the dispersant to improve the coloring of the disperse dye from two aspects, thereby eliminating the cleaning step and achieving a water-saving effect. On the one hand, the chemical reaction is utilized to accelerate the diffusion of the disperse dye wrapped in the dispersant from the pretreatment layer to the polyester layer under the drive of asymmetric wettability; on the other hand, a cross-linked network is formed after the chemical reaction to fix the floating color in the pretreatment layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 The transmission infrared spectra of the vinyl-modified sodium lignin sulfonate and sodium lignin sulfonate prepared in Example 1 are shown.

[0063] Figure 2 Total reflection infrared spectra of the pre-treated layer obtained at different heat treatment times.

[0064] Figure 3 This is a scanning electron microscope (SEM) image of the pre-treated layer prepared in Example 1. DETAILED DESCRIPTION

[0065] The present invention is further described in detail below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0066] Disperse dyes were purchased from Shanghai Anuoqi Group Co., Ltd., foaming agents were purchased from Hangzhou Keying Chemical Co., Ltd., surfactants, hydrophilic polymers, sodium lignin sulfonate, and sodium alginate were purchased from Shanghai MacLean Reagent Co., Ltd., polyester fabric (filament, 65 g / m 2 , 484×346 / 7×7) was purchased from Hongda Weaving Factory.

[0067] Example 1

[0068] Inkjet printing ink preparation:

[0069] (1) Weigh sodium lignin sulfonate and dissolve it in water, add NaOH, heat to 70°C under a nitrogen atmosphere, stir and dissolve, then add vinyl ethylene oxide to carry out a ring-opening reaction for 24 hours, and the obtained reaction solution is dialyzed and purified in deionized water, and vacuum dried at 80°C to obtain vinyl-modified sodium lignin sulfonate.

[0070] The mass ratio of the sodium lignin sulfonate, vinyl ethylene oxide and NaOH is 1:0.3:0.02.

[0071] Instructions attached Figure 1 This is the infrared spectrum of sodium lignin sulfonate before and after vinyl modification. The sample was prepared by KBr tablet method. It can be seen from the figure that after modification, the peak at 3042 cm-1 The characteristic absorption peak of vinyl appeared, indicating that vinyl was successfully introduced into sodium lignin sulfonate. In addition, the absorption peak at 3407 cm -1 、2913cm -1 、1610cm -1 and 1041cm -1 、1197cm -1 , are the stretching vibrations of alcoholic hydroxyl and phenolic hydroxyl, CH stretching vibration of methyl and methylene, characteristic absorption of aromatic ring, and CO stretching vibration of phenolic hydroxyl.

[0072] (2) CI Disperse Yellow 48, vinyl-modified sodium lignin sulfonate, defoamer KYC-710, and deionized water were weighed and mixed to obtain a wet material, which was then placed in a planetary ball mill for ball milling to obtain a liquid disperse dye.

[0073] The mass percentage of each component is as follows: 10wt% CI Disperse Yellow 48, 10wt% vinyl-modified sodium lignin sulfonate, 0.25wt% defoamer KYC-710, and the balance deionized water.

[0074] Ball milling conditions: 600 rpm, grinding ball diameter 200 μm, grinding ball 100 wt% of the wet material mass, grinding time 20 h.

[0075] (3) The components were mixed and filtered according to the following formula to obtain inkjet printing ink: 30 wt% of liquid disperse dye, 12 wt% of ethylene glycol, 0.4 wt% of Tween 80, 0.04 wt% of triethanolamine, 0.2 wt% of defoaming agent KYC-710, and the balance was water.

[0076] The filtration is performed by sequentially using separation membranes with pore sizes selected from 0.8 μm, 0.45 μm, and 0.2 μm to filter the mixed solution.

[0077] Printing process:

[0078] (1) Dissolve silane monomer and polyvinyl alcohol in an alcohol-water mixed solution, stir evenly, add hydrochloric acid (concentration of 35%), and stir to react for 24 hours to obtain silica sol, which is a pretreatment agent; the mass percentage of each component is as follows: 20wt% silane monomer, 8wt% polyvinyl alcohol, 3wt% HCl, and the remainder is an alcohol-water mixed solution.

[0079] The silane monomer is a mixture of vinyl trimethoxysilane: aminomethyl triethoxysilane: N-dimethylaminopropyl-aminopropylmethyl dimethoxysilane: methoxy trimethyl silane: allyloxy trimethyl silane in a molar ratio of 0.8:0.2:6:0.5:0.8.

[0080] The alcohol-water mixed solution is a mixed solution in which the mass ratio of ethanol to water is 1:5.

[0081] (2) The fabric is subjected to padding finishing with the pretreatment agent obtained in step (1), the immersion time is 20 minutes, and the liquid carrying rate is 80%.

[0082] (3) Drying the fabric obtained in step (2) at a temperature of 7° C. for 6 min.

[0083] (4) The fabric was inkjet printed using an Epson R330 inkjet printer at 20°C and 60% relative humidity, and then dried at 70°C for 4 min.

[0084] (5) Spray the aqueous initiator solution evenly on the fabric surface at a spraying rate of 0.5 L / m 2 .

[0085] The aqueous initiator solution is an aqueous solution of ammonium persulfate with a concentration of 2.5 wt%.

[0086] (6) Steam the printed fabric in saturated steam at 102°C and normal pressure for 15 min.

[0087] (7) The fabric was dried at 100°C for 12 min.

[0088] In order to verify the cross-linking reaction during the steam fixation process, the fabric was treated by omitting step (4) and controlling the steaming time in step (6) (0, 8, 15 min). The fabric was then tested by total reflection infrared spectroscopy. The results are shown in the attached figure. Figure 2 As can be seen from the figure, the characteristic absorption peak of vinyl decreases with the increase of steaming time, indicating that more vinyl undergoes polymerization reaction with the extension of steaming time.

[0089] Example 2

[0090] The difference from Example 1 is that the mass ratio of the sodium lignin sulfonate, vinyl ethylene oxide and NaOH is 1:0.2:0.02.

[0091] Example 3

[0092] The difference from Example 1 is that the mass ratio of the sodium lignin sulfonate, vinyl ethylene oxide and NaOH is 1:0.4:0.02.

[0093] Example 4

[0094] The difference from Example 1 is that the mass percentages of the components of the liquid disperse dye are as follows: 10wt% CI Disperse Yellow 48, 5wt% vinyl-modified sodium lignin sulfonate, 0.25wt% defoamer KYC-710, and the balance deionized water.

[0095] Example 5

[0096] The difference from Example 1 is that the mass percentages of the components of the liquid disperse dye are as follows: 10wt% CI Disperse Yellow 48, 15wt% vinyl-modified sodium lignin sulfonate, 0.25wt% defoamer KYC-710, and the balance deionized water.

[0097] Example 6

[0098] Inkjet printing ink preparation:

[0099] (1) Same as Example 1

[0100] (2) CI Disperse Blue 79, vinyl-modified sodium lignin sulfonate, defoamer KYC-710, and deionized water were weighed and mixed to obtain a wet material, which was then placed in a planetary ball mill for ball milling to obtain a liquid disperse dye.

[0101] The mass percentage of each component is as follows: 10wt% CI Disperse Blue 79, 10wt% vinyl modified sodium lignin sulfonate, 0.25wt% defoamer KYC-710, and the balance deionized water.

[0102] Ball milling conditions: 400 rpm, grinding ball diameter 300 μm, grinding ball weight 150 wt% of the wet material mass, grinding time 24 h.

[0103] (3) The components were mixed and filtered according to the following formula to obtain inkjet printing ink: 25 wt% of liquid disperse dye, 15 wt% of 1,4-butanediol, 0.7 wt% of polyethylene glycol, 0.6 wt% of Span 60, 0.07 wt% of triethanolamine, 0.2 wt% of defoaming agent KYC-710, and the balance was water.

[0104] The filtration is performed by sequentially using separation membranes with pore sizes selected from 0.8 μm, 0.45 μm, and 0.2 μm to filter the mixed solution.

[0105] Printing process: same as Example 1

[0106] Example 7

[0107] Inkjet printing ink preparation:

[0108] (1) Same as Example 1

[0109] (2) CI Disperse Red 167, vinyl-modified sodium lignin sulfonate, defoamer KYC-710, and deionized water were weighed and mixed to obtain a wet material, which was then placed in a planetary ball mill for ball milling to obtain a liquid disperse dye.

[0110] The mass percentage of each component is as follows: 10wt% CI Disperse Red 167, 10wt% vinyl modified sodium lignin sulfonate, 0.25wt% defoamer KYC-710, and the balance deionized water.

[0111] Ball milling conditions: 800 rpm, grinding ball diameter 100 μm, grinding ball weight 120 wt% of the wet material mass, grinding time 14 h.

[0112] (3) The components were mixed and filtered according to the following formula to obtain inkjet printing ink: 35 wt% of liquid disperse dye, 10 wt% of glycerol, 0.1 wt% of polyvinyl pyrrolidone, 0.2 wt% of fatty alcohol polyoxyethylene ether, 0.02 wt% of triethanolamine, 0.2 wt% of defoamer KYC-710, and the balance was water.

[0113] The filtration is performed by sequentially using separation membranes with pore sizes selected from 0.8 μm, 0.45 μm, and 0.2 μm to filter the mixed solution.

[0114] Printing process: same as Example 1

[0115] Example 8

[0116] The difference from Example 1 is that the mass percentages of the components of the pretreatment agent in the printing process are as follows: 15wt% silane monomer, 8wt% polyvinyl alcohol, 3wt% HCl, and the remainder is a mixed solution of alcohol and water.

[0117] Example 9

[0118] The difference from Example 1 is that the mass percentages of the components of the pretreatment agent in the printing process are as follows: 25wt% silane monomer, 8wt% polyvinyl alcohol, 3wt% HCl, and the remainder is a mixed solution of alcohol and water.

[0119] Example 10

[0120] The difference from Example 1 is that the silane monomer in the pretreatment agent in the printing process is a mixture of vinyltrimethoxysilane:aminomethyltriethoxysilane:N-dimethylaminopropyl-aminopropylmethyldimethoxysilane:methoxytrimethylsilane:allyloxytrimethylsilane in a molar ratio of 0.8:0.2:4:0.5:0.8.

[0121] Embodiment 11

[0122] The difference from Example 1 is that the silane monomer in the pretreatment agent in the printing process is a mixture of vinyltrimethoxysilane:aminomethyltriethoxysilane:N-dimethylaminopropyl-aminopropylmethyldimethoxysilane:methoxytrimethylsilane:allyloxytrimethylsilane in a molar ratio of 0.8:0.2:8:0.5:0.8.

[0123] Example 12

[0124] The difference from Example 1 is that the mass percentages of the components of the pretreatment agent in the printing process are as follows: 20wt% silane monomer, 10wt% polyethylene glycol, 2wt% HCl, and the remainder is an alcohol-water mixed solution; the alcohol-water mixed solution is a mixed solution with a mass ratio of ethanol to water of 1:3.

[0125] The fabric was subjected to padding finishing using the above pretreatment agent, with an immersion time of 10 minutes and a liquid carrying rate of 60%.

[0126] Example 13

[0127] The difference from Example 1 is that the mass percentages of the components of the pretreatment agent in the printing process are as follows: 20wt% silane monomer, 5wt% polyacrylic acid, 5wt% HCl, and the remainder is an alcohol-water mixed solution; the alcohol-water mixed solution is a mixed solution with a mass ratio of ethanol to water of 1:7.

[0128] The fabric was subjected to padding finishing using the above pretreatment agent, the immersion time was 30 minutes, and the liquid carrying rate was 90%.

[0129] Comparative Example 1

[0130] Sodium alginate paste was prepared as a pretreatment agent. The preparation method was as follows: sodium alginate, silica nanoparticles, and surfactant 1292 were mixed in water. The mass fractions of the components were as follows: 18wt% sodium alginate, 4wt% silica nanoparticles, 3wt% surfactant 1292, and the remainder was water.

[0131] The above paste was used as a pretreatment agent to print fabric according to the printing process of Example 1; since the printed fabric obtained had too much floating color, the steamed fabric needed to be washed (soap washing at 98°C for 5 minutes → cold water washing for 10 minutes) and then dried.

[0132] Comparative Example 2

[0133] Cationic silica sol is prepared as a pretreatment agent. The preparation method is as follows: dissolve tetraethyl orthosilicate, γ-aminopropyltrimethoxysilane, and hexadecyltrimethylammonium chloride in an alcohol-water mixed solution, stir evenly, add hydrochloric acid, and continue stirring for 24 hours to obtain silica sol; the mass fraction of each component is as follows: 16wt% of tetraethyl orthosilicate, 6wt% of γ-aminopropyltrimethoxysilane, 10wt% of hexadecyltrimethylammonium chloride, 5wt% of HCl, and the remainder is an alcohol-water mixed solution; the alcohol-water mixed solution is a mixed solution in which the mass ratio of ethanol to water is 1:5.

[0134] The fabric was printed using the cationic silicon solution as a pretreatment agent according to the printing process of Example 1; since the printed fabric had too much floating color, the steamed fabric needed to be washed (soap washing at 98°C for 5 minutes → cold water washing for 10 minutes) and then dried.

[0135] Comparative Example 3

[0136] The difference from Example 1 is that sodium lignin sulfonate is used as the dispersant instead of vinyl-modified sodium lignin sulfonate.

[0137] Comparative Example 4

[0138] The difference from Example 1 is that the fabric is not pretreated before inkjet printing, and the steamed fabric is washed (soap washing at 98° C.×5 min→cold water washing for 10 min) and then dried.

[0139] Performance evaluation of liquid disperse dyes:

[0140] (1) Particle size test: After diluting the liquid disperse dye paste, the average particle size and dispersion index (PDI) of the sample were measured by dynamic light scattering using a Malvern particle size analyzer at 25°C.

[0141] (2) Stability test: The ground disperse dye paste was sealed in a reagent bottle and allowed to stand at room temperature. A small amount of samples were taken out on the 0th, 15th and 30th days, and the average particle size and dispersion index (PDI) before and after standing were tested.

[0142] Table 1

[0143]

[0144]

[0145] As can be seen from the data, vinyl-modified sodium lignin benzene sulfonate has a better dispersing effect on disperse yellow and disperse blue, and a poorer dispersing effect on disperse red; relative to comparative example 3, the dispersant provided by the present invention has better stability for liquid disperse dyes, because after the introduction of vinyl, the alcohol / phenolic hydroxyl group in the dispersant becomes less, reducing the agglomeration caused by intermolecular hydrogen bonding, increasing the intermolecular steric hindrance, thereby inhibiting the agglomeration during storage; but the more vinyl content, the larger the particle size of the disperse dye, because the higher the vinyl content, the worse the hydrophilicity of the dispersant. When the amount of dispersant is too much, the sodium ions ionized in the system will compress the double electric layer on the surface of the disperse dye, weakening the stabilizing effect of electrostatic repulsion, and the viscosity of the dispersed system will also increase, causing the disperse dye agglomeration and grinding media to be unable to separate, thus leading to an increase in the average particle size.

[0146] Evaluation of physical and chemical properties of inkjet printing ink:

[0147] (1) Zata potential: The disperse dye ink was diluted 1000 times in deionized water and measured at 25°C using a Malvern Zeta potential analyzer.

[0148] (2) Surface tension: The test was carried out using a DCAT21 surface tension meter at 20°C.

[0149] (3) Viscosity: The viscosity was measured using a Rhellab QC rotational viscometer at 20°C and a rotation speed of 60 rpm.

[0150] (4) Conductivity: Tested using ST3100C conductivity meter.

[0151] Table 2

[0152]

[0153]

[0154] It can be seen from the data in Table 2 that the physical and chemical properties of the inkjet printing ink provided by the present invention all meet the application requirements.

[0155] Printing performance evaluation:

[0156] (1) Printing outline clarity: A single-color straight line with a width of 1 pound was printed on polyester fabric using an Epson R330 inkjet printer. After printing, the fabric was dried at 90 °C for 60 seconds, then steamed in saturated steam at 102 °C for 10 minutes, and then dried at 100 °C for 5 minutes. The line width was observed using a three-dimensional ultra-depth digital microscope, and the line width was analyzed using image analysis software. The line width change rate (W) was calculated according to formula (I).

[0157] W=(D-D0) / D0×100% (I)

[0158] Where D0 is the printed line width, 353 μm; D is the measured line width.

[0159] (2) Determination of apparent color depth (K / S value): The apparent color depth K / S value of the blended fabrics obtained in the examples and comparative examples was tested using a Datacolor 650 colorimeter. The D65 light source and 10° viewing angle were selected to measure the K / S value at the wavelength of maximum absorption of the dyed fabric. Ten points were randomly selected for each sample for measurement, and the average value was calculated.

[0160] (3) Fabric stiffness determination: According to GB / T18318-2009 “Determination of the bending length of textile fabrics”, the warp and weft bending lengths of the fabric were tested using a YG(B)022D fabric stiffness tester and the average value was taken. The sample size was 25 cm × 2.5 cm.

[0161] (4) Color fastness test: The color fastness to washing with soap of dyed fabrics shall be tested in accordance with GB / T3921-2008 “Textiles - Tests for Color Fastness - Color Fastness to Washing with Soap”; the color fastness to rubbing of dyed fabrics shall be tested in accordance with GB / T3920-2008 “Textiles - Tests for Color Fastness - Color Fastness to Rubbing”.

[0162] Table 3

[0163]

[0164] It can be seen from the data in the table that the pretreatment agent provided by the present invention has lower fabric stiffness than the commonly used paste of Comparative Example 1 and the silica sol paste of Comparative Example 2 with unadjusted functionality ratio, that is, the wearing performance of the fabric is better. In addition, since the pretreatment agents of Comparative Examples 1 and 2 do not contain vinyl, they cannot be used as adhesives to fix floating colors, so their color fastness is low and the K / S value is low. In Comparative Example 3, vinyl-modified sodium lignin sulfonate is not used as a dispersant, resulting in a low K / S value and low color fastness. The reason is that the dispersant without vinyl cannot quickly release the disperse dye through the chemical reaction process, so the disperse dye diffuses into the fiber at a slow speed and a low degree, resulting in a large amount of floating color.

[0165] The more silane monomers there are in the pretreatment agent, the line width change rate shows a pattern of first decreasing and then increasing. The reason is that if there are too few silane monomers, the viscosity of the pretreatment agent is too low, and a uniform, flat, isotropic pretreatment layer cannot be formed on the fabric surface, resulting in ink penetration; if there are too many silane monomers, the viscosity of the pretreatment agent is too high, its fluidity decreases, and a flat pretreatment layer cannot be formed. The more silane monomers with an alkoxy number of 2 in the pretreatment, the lower the stiffness of the fabric, because the crosslinking density of the pretreatment layer is lower; but the line width change rate shows a trend of first increasing and then decreasing with the increase of crosslinking density, because the crosslinking density affects the viscosity of the pretreatment agent; the K / S value of the fabric increases with the increase of crosslinking density, because when the crosslinking density is low, the fluidity of the pretreatment layer is enhanced, which is not conducive to the formation of a pore structure with uniform pore size and uniform distribution, and slows down the diffusion of disperse dyes. Attachment Figure 3 This is a SEM image of the pretreatment layer of Example 1. It can be seen from the figure that the pretreatment layer presents a flat modified layer on the fabric surface and has a uniformly distributed porous structure. The porous structure serves as a diffusion channel for disperse dyes, which is conducive to obtaining a printed fabric with a high coloring rate.

[0166] The above contents are further detailed descriptions of the present invention in combination with specific preferred technical solutions, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For professionals and technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A liquid disperse dye, characterized in that: The composition includes the following components by weight percentage: 8wt%~12wt% disperse dye, 5wt%~15wt% vinyl modified sodium lignin sulfonate, 0.1wt%~0.5wt% defoamer, and the balance is deionized water; the average particle size of the liquid disperse dye is 100~300nm; the particle size dispersion index PDI is 0.2~0.25; The method for preparing vinyl-modified sodium lignin sulfonate comprises the following steps: weighing sodium lignin sulfonate and dissolving it in a solvent, adding alkali, stirring and dissolving it under an inert atmosphere, then adding vinyl ethylene oxide to carry out a ring-opening reaction, and after the reaction is completed, purifying and drying the reaction solution to obtain vinyl-modified sodium lignin sulfonate.

2. A liquid disperse dye according to claim 1, characterized in that, The solvent is selected from at least one of ethanol, water, N,N-dimethylformamide, chloroform, and dimethyl sulfoxide; The base is selected from one of NaOH and KOH; The ring-opening reaction refers to reacting at 60-80°C for 24-36h; The mass ratio of the sodium lignin sulfonate, vinyl ethylene oxide and alkali is 1:0.2-0.4:0.

02.

3. A disperse dye printing ink, comprising a liquid disperse dye according to any one of claims 1 to 2, characterized in that: The disperse dye printing ink comprises the following components calculated by mass percentage: 25wt%~35wt% of liquid disperse dye, 10wt%~15wt% of moisturizing agent, 0wt%~0.7wt% of viscosity regulator, 0.2wt%~0.6wt% of surfactant, 0.02wt%~0.07wt% of pH regulator, 0.1wt%~0.3wt% of defoaming agent, and the balance is water.

4. A disperse dye printing ink according to claim 3, characterized in that: Disperse dye printing ink has the following characteristics: Zeta potential is -40~-56mV; Surface tension is 30~35mN / m; Viscosity: 1.5~2.2mPa·s; The conductivity is 6~7μS / cm; The pH value is 7-9.

5. A disperse dye printing ink according to claim 3, characterized in that: The moisturizer is selected from at least one of ethylene glycol, butylene glycol, propylene glycol, glycerin and diethylene glycol; The viscosity modifier is selected from at least one of polyethylene glycol and polyvinyl pyrrolidone; The surfactant is selected from at least one of fatty alcohol polyoxyethylene ether, alkyl glycoside, Span60, Tween80, and OP-10; The pH adjuster is at least one selected from diethanolamine, triethanolamine, ammonia water, and trimethylamine.

6. A water-free inkjet printing process, using the disperse dye printing ink according to any one of claims 3 to 5 for inkjet printing, characterized in that: The water-free inkjet printing process comprises the following steps: padding pretreatment→first drying→inkjet printing→second drying→initiator spraying→steaming fixation→third drying; the pretreatment agent used in the padding pretreatment comprises the following components by mass percentage: 15wt%~25wt% of silane monomer, 5wt%~10wt% of hydrophilic polymer, 2wt%~5wt% of catalyst, and the remainder is a mixed solution of alcohol and water; The silane monomer also has the following characteristics: Feature 1: The molar ratio of the silane monomer with 1 alkoxy group, the silane monomer with 2 alkoxy groups, and the silane monomer with 3 alkoxy groups is 1:4~8:1~2; Feature 2: Contains at least one vinyl silane monomer.

7. A water-free inkjet printing process according to claim 6, characterized in that: The alcohol in the alcohol-water mixed solution is selected from ethanol, methanol, and ethylene glycol, and the mass ratio of alcohol to water is 1:3-7; The catalyst is selected from one of hydrochloric acid, acetic acid, sodium hydroxide and ammonia; The hydrophilic polymer is selected from at least one of polyvinyl alcohol, polyethylene glycol, sodium hyaluronate and polyacrylic acid.

8. A water-free inkjet printing process according to claim 6, characterized in that: Spraying the initiator means spraying the aqueous initiator solution uniformly on the fabric surface in a spraying manner, wherein the aqueous initiator is selected from at least one of ammonium persulfate, sodium persulfate, and potassium persulfate; the concentration of the initiator aqueous solution is 1wt%~5wt% solution; the spraying amount of the initiator aqueous solution is 0.4~0.6L / m 2 .

Citation Information

Patent Citations

  • Dispersed dye steaming-free printing paste

    CN102691217A

  • Trace amount of printing paste and preparation method and application thereof

    CN105113284A